Pengetahuan Tugas dan Fungsi Organisasi Di Desa Pematang Balam Kabupaten Bengkulu Utara - Ulandari, Cici; Parwito, Parwito; Pratomo, Bakat Seno; Franro, Franro; Rohati, Nely (Gayaku Publisher, 2022)
The purpose of the service of making the Pematang Balam village structure board is so that there is a clear archive related to Pematang Balam village officials and to provide clarity to the community regarding influential people in Pematang Balam village. This method of giving the structure board directly to the village head and village officials at the Pematang Balam village office. The target to be achieved is the village office, in order to create security for a village, because all tasks have been divided according to the structure that has been made.